Spatiotemporal Application of the Standardized Precipitation Index (SPI) in the Eastern Mediterranean - Tsesmelis, Demetrios E.; Leveidioti, Ioanna; Karavitis, Christos A.; Kalogeropoulos, Kleomenis; Vasilakou, Constantina G.; Tsatsaris, Andreas; Zervas, Efthimios (Climate (Basel), 2023)
The ever-increasing need for water, the alteration in the climate, and its observed changes over recent years have triggered a lot of research studies associated with the phenomenon of drought. Within the wider geographical region of the Mediterranean, the relevant scientific subject seems to be of great interest, since it is undoubtedly related to a number of severe socio-economic consequences. This present effort focuses on the evolution of this particular phenomenon over time, within the borders of nine different countries in the Eastern Mediterranean (Athens, Greece—Europe; Constantinople, Turkey—Asia; Nicosia, Cyprus—Europe; Jerusalem, Israel—Asia; Amman, Jordan—Asia; Damascus, Syria—Asia; Beirut, Lebanon—Asia; Cairo, Egypt—Africa; and Tripoli Libya—Africa). By applying the Standard Precipitation Index (SPI), examining precipitation data at the month level (January 1901 to December 2020), and utilizing the Inverse Distance Weighted (IDW) method, the spatio–temporal variability of drought events in the Eastern Mediterranean area was studied. In Jerusalem, long-term droughts presented a higher than usual volume, in accordance with applying the 12- and 24-month SPI, starting from the mid-20th century. Similarly, the region of Damascus presented a similar pattern to those in Beirut, Amman, and Jerusalem. An upward trend in the frequency of extreme drought events was observed for the last thirty years. The same trend seems to be true in terms of the duration of dry periods. Drought events have also been observed in the central, southern, and eastern regions of Turkey. A downward trend was observed in Cairo based on a trend analysis of its monthly precipitation.